2004
DOI: 10.1128/jvi.78.15.8210-8218.2004
|View full text |Cite
|
Sign up to set email alerts
|

Oral Immunization with RecombinantListeria monocytogenesControls Virus Load after Vaginal Challenge with Feline Immunodeficiency Virus

Abstract: Recombinant Listeria monocytogenes has many attractive characteristics as a vaccine vector against human immunodeficiency virus (HIV). Wild-type and attenuated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 78 publications
1
43
0
Order By: Relevance
“…Three months after oral immunisation with a recombinant L. monocytogenes that expresses the FIV Gag and delivers an FIV Env-expressing DNA, cats were vaginally challenged with a molecular clone of FIV. Whilst virus was isolated from four of the five immunised cats, further analysis indicated that viral load was reduced [48]. Taken together, these studies highlight the potential of the mucosal route of immunisation and support the widely held dogma that live vaccines are more effective than killed or subunit vaccines.…”
Section: Induction Of Mucosal Immune Responsessupporting
confidence: 52%
See 1 more Smart Citation
“…Three months after oral immunisation with a recombinant L. monocytogenes that expresses the FIV Gag and delivers an FIV Env-expressing DNA, cats were vaginally challenged with a molecular clone of FIV. Whilst virus was isolated from four of the five immunised cats, further analysis indicated that viral load was reduced [48]. Taken together, these studies highlight the potential of the mucosal route of immunisation and support the widely held dogma that live vaccines are more effective than killed or subunit vaccines.…”
Section: Induction Of Mucosal Immune Responsessupporting
confidence: 52%
“…Fewer studies have investigated the numbers of IEL in the large intestine, but Dobbins [17] reported 5% epithelial cells in man and Atkins and Schofield [3] 2% epithelial cells in dogs. The numbers of IEL in the feline large intestine are similar (about 4% epithelial cells) [48].…”
Section: Inductive and Effector Sitesmentioning
confidence: 96%
“…The attenuated strain of L. monocytogenes described here, L. monocytogenes dal dat/pRRR, which utilizes a host-induced recombination system to regulate D-alanine availability, appears to provide good immunogenicity while remaining highly attenuated. Therefore, it may be a promising vaccine against listeriosis or act as a vaccine carrier for use against other intracellular bacterial pathogens (31), viruses (19,22,28,48,54), tumors (6,38), and parasites (52).…”
Section: Discussionmentioning
confidence: 99%
“…Bypassing the gastrointestinal tract could lead to differences in dissemination. Moreover, oral immunization of L. monocytogenes as a vaccine is clearly the preferred route, not only because of the convenience of administration, but also because of the possibility of inducing mucosal immunity at the site of infection for many viral pathogens (19,22,48,54). Using an L. monocytogenes dal dat-based recombinant of L. monocytogenes expressing HIV type 1 gag, we previously showed that oral immunization of BALB/c mice generated protective mucosal anti-HIV gag CD8 ϩ T lymphocytes, thus supporting the possible development of an oral anti-HIV vaccine (18,(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Head-to-head comparisons of intranasal and parenteral routes for delivery of recombinant Listeria vectors have not been reported. The recombinant Listeria vaccine vectors for infections reported to date by other investigators have been based on either wild-type Listeria (2,29) or Listeria deleted of the essential D-alanine synthesis pathway (9), thus raising safety concerns (with the wild type) or requiring special D-alanine supplemental treatments during vaccination of animals (dal dat mutants). We recently demonstrated that attenuated the Listeria ⌬actA prfA*strain is a promising vaccine vector, since r-Listeria ⌬actA prfA* secretes Ͼ100-fold-higher levels of vaccine immunogens in broth culture than wild-type r-Listeria or r-Listeria ⌬actA, and it elicits much higher magnitudes of immunogen-specific humoral and cellular immune responses after intravenous vaccination of mice than those induced by r-Listeria ⌬actA (32).…”
Section: Discussionmentioning
confidence: 99%